Characteristics of promising lines of spring sphaerococcum wheat (Triticum sphaerococcum Percival) according to productivity and grain quality indicators - Danil F. Askhadullin; Damir F. Askhadullin; N. Z. Vasilova; I. I. Khusainova; G. R. Gaifullina; M. R. Tazutdinova; E. S. Kirillova; A. R. Khairullina; R. Kh. Idiatova; G. R. Saubanova; A. A. Askarova (Зерновое хозяйство России, 2024)
There has been carried out an estimation of promising spring wheat lines of the species Triticum sphaerococcum (sphaerococcum wheat, T.sph) in a competitive variety testing in Tatarstan in 2022–2023, in comparison with the sphaerococcum wheat variety ‘Sakara’ and the common wheat variety ‘Yoldyz’ (standard of the State Variety Commission). Productivity of the promising lines was inferior to the standard spring common wheat variety ‘Yoldyz’ by 23–31 %. The productivity of these lines in 2022 did not differ significantly from the sphaerococcum wheat variety ‘Sakara’ and amounted to 3.27...3.89 t/ha. In 2023, productivity of the lines ‘Sh-359-11-8-2’ and ‘Sh-15-15-28’ was significantly higher compared to the variety ‘Sakara’ by 0.56 t/ha and by 0.31 t/ha, respectively. The developed lines T.sph have a high protein and gluten percentage in grain. The protein percentage in grain averaged from 16.2 % for the line ‘Sh-15-15-13’ to 19.2 % for the line ‘Sh-15-15-12’, gluten percentage in grain ranged from 30.2 % for the line ‘Sh-15-15-13’ to 33.5 % for the line ‘Sh-15-15-28’, which corresponds to the standards of “strong wheat”. The lines T.sph have a large grain size of 805–813 g/l, which is significantly higher than that of the variety ‘Sakara’. The line ‘Sh-359-11-8-2’ has 1000-grain weight of 35.8 g, at the level of the common wheat variety ‘Yoldyz’, other lines are inferior in 1000-grain weight to the variety ‘Yoldyz’ by 3.7...11.6 g. The line ‘Sh-15-15-28’ has the maximum grain uniformity of 95.9 %, which is significantly higher than that of the varieties ‘Yoldyz’ and ‘Sakara’ by 10.4 and 12.6 %, respectively. The lines T.sph differ significantly according to the rheological properties of the dough. The flour strength varied from 95 u.a. of the line ‘Sh-15-15-12’ to 300 u.a. of the line ‘Sh-359-11-8-2’, the degree of dough dilution was from 26 u.f. of the line ‘Sh-359-11-8-2’ to 113 u.f. of the line ‘Sh-15-15-13’. According to protein and gluten percentage, dough dilution and resilience, and P/L ratio, the line ‘Sh-359-11-8-2’ meets the classification standards of “excellent improver.” The general baking assessment for the lines T.sph was 4.25–4.74 points, and the baked bread was of good quality.